PERAN STAKHOLDERS DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA LEREP KABUPATEN SEMARANG - Afrida Andriyani, Lailliya; Yuniningsih, Tri; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Semarang Regency has become destination for tourists. The emergence of tourist saturation in visiting artificial tourist areas has given birth to a new concept of tourism known as village tourism. One of the tourist villages being developed by Semarang Regency Government is Lerep Tourism Village. However, the development of the Lerep Tourism Village has not yet reached an optimal level of development. Therefore, this research aims to identify stakeholders, analyze the role stakeholders, and analyze supporting&inhibiting factors in tourism development in the Lerep Tourism Village. Researchers used descriptive qualitative research methods. The research results show that the stakeholders involved in tourism development in the Lerep Tourism Village are divided into four categories, namely: key players, subjects, context setters, crowds. The role of stakeholders is divided into five types, namely: policy creator (Lerep Village Government, Dinas Pariwisata, and DISPERMASDES); coordinator (Dinas Pariwisata, DISPERMASDES, and BUMDES); facilitators (Dinas Pariwisata, DISPERMASDES, Lerep Village Government, Pokdarwis Rukun Santoso, PLN, BRI, JawaPos, and KKN UNDIP); implementers (Pokdarwis Rukun Santoso, Pokdarwis Indrokilo, Pokdarwis Soka, and Karang Taruna); and accelerators (Lerep Village Government, Pokdarwis Rukun Santoso, Karang Taruna Lerep Village, Jawa Pos Semarang, and KKN UNDIP). Then, the supporting factors in developing tourism in the Lerep Tourism Village consist of the creativity of the management and the existence of trust. Meanwhile, inhibiting factors consist of misunderstanding and lack of organizational strengthening. Recommendations that can be given are to improve relations between stakeholders and improve communication so that the development of the Lerep Tourism Village can run optimally.